The person in history - Tullume Fenco, Eliana (2021)
The person throughout of the history, is a short essay that shows the revolts and attacks towards a single concept: Person. In this way, man faces two positions: From traditional philosophy and from modern currents; that is to say, while philosophy needs to explore those little-expanded concepts about the person, the currents will take advantage of these voids to limit man to thoughts, emotions and pleasures, as well as to question his dignity and integrity. In sequence, despite the different perspectives of these movements, both conclude that man is an indispensable element in society. Discovering the true human essence makes it possible to find the good, the truth and the beauty; For this reason, reflecting on man allows to reach an extra connection with the creator, who through the use of powers shapes his projects on each one.